Análise da amplitude da pegada sobre indicadores neuro musculares no powerlifting paralímpico - Santos, Marcelo Danillo Matos dos (2019)
Objective: Investigate the effects in different amplitudes of the grip width in Powerlifting Paralympic (PP) athletes on dynamic and isometric muscular strength, rate of force development and muscular electrical activity. Methods: We evaluated 12 PP athletes participating in the extension project of the Federal University of Sergipe. Age range (25.40 ± 3.30 years), body mass (70.30 ± 12.15 kg) and time of experience in the sport (2.45 ± 0.21 years). The subjects of this study are competitors at the national level, classified and ranked among the top ten of their respective categories. To evaluate the dynamic (FDM) and isometric forces (FIM), velocity, time, rate of force development (TDF) and muscular activity, a linear encoder, force sensor, and electromyograph were used. The evaluation occurred during five weeks, in first week was establish for one-repetition maximum test (1RM) and familiarization. The remaining weeks were establish to evaluations with different widths of the grip; 1x, 1.3x, 1.5x of the bi-acromial distance (DBA) and 81,0 cm between the index fingers (maximum allowed in the sport). Results: Study 1 there was a significant difference (p = 0,019) in increase of velocity 1.52 ± 0.36 m/s for relative maximum dynamic force with 25% of the maximum dynamic force with the 1.5x grip width of the DBA, significant results in time (ms) (p = 0,030) (p = 0,032) (p = 0,030) with the 1.5x DBA grip for isometric strength with 30%, 50% and 100% (187.44 ± 85.81 ms, 312.66 ± 142.92 ms, 626.00 ± 285,98 ms). No difference between types of strength and muscle activity for both grip widths. Study 2 There were no differences between the different widths of the grip and distances from the bar to the chest (DBP) in FIM. The 1x DBA grip produced more FIM and TDF with the bar leaning against the chest (BP), however, there was a predisposition for grips of 1.3x DBA, 1.5x DBA and 81cm to generate more FIM and TDF (10, 20, 30 cm DBP, 653,84 ± 256,62 N, 859,25 ± 293,95 N, 1130.28 ± 390.2 N and 20 cm DBP, 2029.22 ± 1753.37; 30 cm DBP 1609.66 ± 1555.00 N.ms-1). Conclusion: The grip width of 1.5x DBA provided increase in FDM and FIM, speed, time for maximum PP strength, greater activation of the pectoralis major sternal part (PME) and anterior deltoid (DA). Larger grips such as 1,3x DBA, 1,5x DBA and 81 cm promoted FIM in relation to 10, 20, 30 cm DBP. Except for FIM BP where the 1x DBA grip promoted the highest FIM. The 1x DBA grip increased the TDF with BP and with 10 cm DBP, for 20 and 30 cm DBP the 1,3x DBA grip and 1,5x DBA generated more TDF in the PP athletes.